2007
DOI: 10.2175/193317707x256919
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary Phosphorus Removal Pilot Tests Technology Limits In Coeur D'Alene, ID

Abstract: Spokane River dischargers face restrictive phosphorus discharge limits that are technically challenging. A tertiary phosphorus removal pilot at the wastewater treatment plant was conducted between June and October 2006. Technologies from four different manufacturers were tested on their ability to reliably produce effluent total phosphorus (TP) concentrations of less than 50 µg/L and less then 10 µg/L. The demonstration pilot showed that effluent total phosphorus concentration of less than 50 µg/L can be produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A similar but shorter pilot study of three tertiary pilot units in Marlborough, MA, for a domestic wastewater with nearly 50% commercial and industrial components revealed intermittent recalcitrant phosphorus concentrations up to 500 µg/L (Lancaster and Madden, 2008). It is suspected that recalcitrant phosphorus is mostly, if not entirely, comprised of dissolved organic phosphorus (Neethling, et al, 2007). Some industrial effluents can contain 1,000-2,000 µg/L DNRP.…”
Section: Recalcitrant Dissolved Nonreactive Phosphorus (Rdnrp)mentioning
confidence: 97%
See 3 more Smart Citations
“…A similar but shorter pilot study of three tertiary pilot units in Marlborough, MA, for a domestic wastewater with nearly 50% commercial and industrial components revealed intermittent recalcitrant phosphorus concentrations up to 500 µg/L (Lancaster and Madden, 2008). It is suspected that recalcitrant phosphorus is mostly, if not entirely, comprised of dissolved organic phosphorus (Neethling, et al, 2007). Some industrial effluents can contain 1,000-2,000 µg/L DNRP.…”
Section: Recalcitrant Dissolved Nonreactive Phosphorus (Rdnrp)mentioning
confidence: 97%
“…The nonreactive phosphorus is believed to be primarily organic in nature, but could contain other complexed phosphorus compounds. Similar to EDON, the following definitions are used for phosphorus species in the effluent (adapted from Neethling et al, 2007) -see also Figure 4-2:…”
Section: Calculated From Measurement That Includes (A)+(b) B Calcmentioning
confidence: 99%
See 2 more Smart Citations
“…Lower phosphorus concentration has been achieved at pilot scale. For example, some researchers have proven the ability to produce effluent TP less than 0.05 mg/L (Benisch et al 2007;Hugh & Tozer 2007). Hook & Ott (2001) selected six filter products to test TP removal using the Metro Wastewater Treatment Plant effluent as the experimental feed.…”
Section: Introductionmentioning
confidence: 99%